2016
DOI: 10.1038/nature20112
|View full text |Cite
|
Sign up to set email alerts
|

Wild monkeys flake stone tools

Abstract: * These authors contributed equally to this work. Paleoanthropologists use the distinctive characteristics of flaked stone tools both to distinguish them from naturally broken stones, and to interpret the behaviour of the hominins that produced them 4 . Suggested hallmarks of the earliest stone tool technology include (i) controlled, conchoidal flaking 5 , (ii) production of sharp cutting edges 6 , (iii) repeated removal of multiple flakes from a single core, (iv) clear targeting of core edges, and (v) adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
151
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(162 citation statements)
references
References 24 publications
8
151
0
3
Order By: Relevance
“…However, it seems that between a pounding-like activity such as nut cracking and an intentional flaking activity there is an ‘intermediate step’, a stage in which the evolution of certain aspects related to the cognitive capabilities of hominins would have played an important role, and in which hominins would have acquired the skills necessary to systematically knap stone tools [2, 39]. However, this stage would be difficult to recognize in the fossil record because of the lack of archaeologically visible remains (but see Proffitt et al, [81]).…”
Section: Resultsmentioning
confidence: 99%
“…However, it seems that between a pounding-like activity such as nut cracking and an intentional flaking activity there is an ‘intermediate step’, a stage in which the evolution of certain aspects related to the cognitive capabilities of hominins would have played an important role, and in which hominins would have acquired the skills necessary to systematically knap stone tools [2, 39]. However, this stage would be difficult to recognize in the fossil record because of the lack of archaeologically visible remains (but see Proffitt et al, [81]).…”
Section: Resultsmentioning
confidence: 99%
“…Percussive techniques like those observed in non-human primates may have been the precursor to the earliest hominin stone tool making around 3 Ma [1014]. Thus, a better understanding of tool use in non-human primates helps us to validate and critically evaluate our interpretations of the fossil and archaeological records [15]. Further, comparative studies of tool use in extant primates allow us to better interpret and understand what early lithic technologies looked like, how they may have been used by ancient hominins, as well as how site preservation and visibility (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Proffitt, Luncz, Falótico, Ottoni, de la Torre, and Haslam (2016) recently reported in Nature that wild capuchin monkeys unintentionally produce sharp stone flakes, but they do not purposefully use these flakes for cutting. In an associated opinion piece, the Editors of Nature downplayed any connection between these findings and the development of human stone tool production and use.…”
mentioning
confidence: 99%
“…Specifically, Proffitt et al (2016) reported that wild bearded capuchin monkeys (Sapajus libidinosus) in Brazil “deliberately break stones unintentionally producing … sharp-edged flakes and cores that have the characteristics and morphology of intentionally produced hominin tools chipped from larger rock cores” (p. 85, italics added). Stone breaking by capuchins is not remarkable in and of itself.…”
mentioning
confidence: 99%